Efektivitas Program Posyandu untuk Meningkatkan Tumbuh Kembang Balita 0-2 Tahun di Puskesmas Padang Bulan - Sadiah Muayyadah; Agus Suriadi (Yayasan Literasi Sains Indonesia, 2024)
Golden period for toddler aged 0-5 years old is a period when growth and development increasing rapidly, therefore additional attention is needed from the parents. If on this golden period toddler experience undernutrition, their growth and development would be difficult to resolve. In this case, monitoring the growth and development of toddlers is very important because it has a significant impact on the health, development and quality of life of toddlers. This research aim to know the effectiveness correlation of posyandu program with growth and development of toddler within age of 0-2 years at Padang Bulan Health Center. Samples in this reasearch are 48 samples. Data analysis used is Chi-square test with P < 0,50. Based on the results and discussion of the research, it can be concluded that there is an effective relationship between the posyandu program and the growth and development of toddlers, where the nutrition posyandu has a value of 0.003, the immunization posyandu has a value of 0.017, and routine participation in the posyandu program has a value of 0.001. Therefore, the hypothesis of this research Ho is rejected, Ha is accepted. Posyandu program has an important part in supporting toddler's growth and development through comprehensive care, parents education, and routine evaluation that can help with early health problem detection